2001
DOI: 10.1177/106907270100900206
|View full text |Cite
|
Sign up to set email alerts
|

The Career Assessment Diagnostic Inventory: A New Career Indecision Assessment Tool

Abstract: and Baylor College of MedicineCareer decision making is an important aspect of life. At some point, one must decide what type of job to apply for or whether to seek the education required for a specific career. Many individuals struggle with these decisions. However, multidimensional measures of uncertainty are needed in providing guidance to such persons, because it appears that the indecision phenomenon is multidimensional and not restricted only to a need for career information. The present study evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
6
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
4
6
0
Order By: Relevance
“…Finally, convergent validity of the Italian version of the CFI was examined using zero-order correlations between the four subscales of CFI and other convergent scales concerning the constructs of trait anxiety, generalized indecisiveness, lack of information about occupations, and lack of information about myself. The results confirmed our hypotheses and they were in line with previous studies conducted in different countries (e.g., Chartrand et al, 1990; Vidal-Brown & Thompson, 2001). In particular, data showed that CFI career choice anxiety positively correlated with trait anxiety, as well as with indecisiveness, lack of information about occupations, and lack of information about myself.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Finally, convergent validity of the Italian version of the CFI was examined using zero-order correlations between the four subscales of CFI and other convergent scales concerning the constructs of trait anxiety, generalized indecisiveness, lack of information about occupations, and lack of information about myself. The results confirmed our hypotheses and they were in line with previous studies conducted in different countries (e.g., Chartrand et al, 1990; Vidal-Brown & Thompson, 2001). In particular, data showed that CFI career choice anxiety positively correlated with trait anxiety, as well as with indecisiveness, lack of information about occupations, and lack of information about myself.…”
Section: Resultssupporting
confidence: 93%
“…In particular, data showed that CFI career choice anxiety positively correlated with trait anxiety, as well as with indecisiveness, lack of information about occupations, and lack of information about myself. The same results were found by Chartrand and colleagues (1990), while Vidal-Brown and Thompson (2001) in a sample of college students found higher correlations-but in the same direction of our results-between CFI career choice anxiety and career decision-making anxiety (r ¼ .77) and career commitment anxiety (r ¼ .69), respectively. Furthermore, generalized indecisiveness negatively correlated with indecisiveness, as well as with trait anxiety, lack of information about occupations, and lack of information about myself.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The research generally and consistently indicates that anxiety is positively related to college students’ career indecision (Chartrand, Robbins, Morrill, & Boggs, ; Fuqua, Blum, & Hartman, ; Fuqua, Newman, & Seaworth, ; Miller & Rottinghaus, ). More specifically, career‐related anxiety is negatively associated with self‐exploratory and career information‐seeking behavior (Germeijs, Verschueren, & Soenens, ), career choice certainty and vocational identity (Vidal‐Brown & Thompson, ), coping and perceived control (Weinstein, Healy, & Ender, ), and general career decision making (Saka, Gati, & Kelly, ).…”
mentioning
confidence: 99%